2008
DOI: 10.1509/jimk.16.1.39
|View full text |Cite
|
Sign up to set email alerts
|

Brand Origin Identification by Consumers: A Classification Perspective

Abstract: This is the published version of the paper. This version of the publication may differ from the final published version. Permanent repository link: http://openaccess.city.ac.uk/17981/ Link to published version: http://dx. The authors apply a classification perspective to (1) examine the extent to which consumers can identify the correct country of origin (COO) of different brands of consumer durables, (2) investigate the factors facilitating/hindering correct COO identification , and (3) trace the implications… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
256
3
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 239 publications
(293 citation statements)
references
References 69 publications
7
256
3
6
Order By: Relevance
“…Indeed, ethnocentric consumers may perceive such brands contributing to their local and regional economy. Thus, Sony's brand was chosen because it is technologically sophisticated in which its COO and COP may be highly diagnostic information for consumer preferences and purchase decision (Balabanis and Diamantopoulos 2008).…”
Section: Consumer Ethnocentrismmentioning
confidence: 99%
“…Indeed, ethnocentric consumers may perceive such brands contributing to their local and regional economy. Thus, Sony's brand was chosen because it is technologically sophisticated in which its COO and COP may be highly diagnostic information for consumer preferences and purchase decision (Balabanis and Diamantopoulos 2008).…”
Section: Consumer Ethnocentrismmentioning
confidence: 99%
“…"Consumers either have limited recognition of brand origins or find such information relatively unimportant and thus unworthy of retention in memory." Balabanis and Diamantopoulos (2008) supported Samiee et al's (2005) conclusion after their investigation of consumers' ability to classify correctly different brands within a specific product category according to their COBs. They concluded that the consumers' overall ability to identify COB was limited.…”
Section: Conceptual Model and Propositionsmentioning
confidence: 79%
“…During the examination of the potential transfer of country image association to brand evaluations and behavioral outcomes, researchers should recognize that not all respondents may associate the brand with the correct COO (the accurate COB). Researchers' presenting respondents with both a list of brands and a list of associated countries compromises the validity of empirical results (Balabanis and Diamantopoulos, 2008). Biasing respondents by mentioning country names is a key shortcoming in COB research (Samiee, 2011).…”
Section: Conceptual Model and Propositionsmentioning
confidence: 99%
“…Such preference may also be due to past history of colonialism in Malaysia (Mandal, 2000) that induces perception of the superiority of Westerners/Western language hence Western brand names are observed to carry a higher prestige (Marcoux, Filialtrault, & Che'ron, 1997). Malaysians perceived them to be of high quality foreign products (Liefeld, 2004;Balabanis and Diamantopoulos, 2008). If a brand name is perceived as foreign, it then brings all the appropriate connotations (quality, glamour, and price) that set it apart from a local brand (Alden, Steenkamp, & Batra, 1999;Batra et al, 2000).…”
Section: International Journal Of Research Studies In Management 53mentioning
confidence: 99%